Development and Validation of Poksd-Porsd Protocol Assessment of Engineering in Elementary Classroom - C Anwar; W Sopandi; U S Sa’ud; W T Pratiwi; H Inderawan (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
The aim of this study was to develop and validate classroom observation instruments designed to reveal the emergence of engineering activities in primary school teachers in project-based learning. The instruments developed included the elementary school classroom observation protocol sheet (POKSD) and the elementary school engineering observation protocol assessment (PORSD). Task items were arranged based on indicators adapted from COPUS (Classroom Observation Protocol for Undergraduate STEM) items. The initial design of the instrument was consulted with three experts based on learning objectives. The instrument was then validated by three experts in the field of basic education. The instrument test was conducted on teachers and 5th-grade students of UPI Bandung Laboratory (N = 1). POKSD and PORSD were assessed by three raters. Scores from the three raters were then analyzed using two-way ANOVA. The results showed that the intra-class correlation of performance assessment instruments was adequate (ICC = 0.773). The findings of this study demonstrated that the instrument was reliable and could be used for the emergence of engineering activities in elementary school teachers.